"Warning for Bahians": stigma and prejudice against new immigrants in Brusque-SC (PerCursos, 2023)
This article aims to understand the presence of northeastern migrants in the municipality of Brusque, a city of Germanic colonization in the state of Santa Catarina. The state of Bahia, located in the Northeast Region of Brazil, is traditionally known as an area of migratory movements. Since the mid-twentieth century, many Bahians have migrated to other regions of Brazil in search of new life opportunities, since migration is motivated by factors such as drought, economic stagnation and high levels of unemployment. At the beginning of the 21st century, the migratory displacements of Bahians, one move towards a new direction: the south of Brazil. In this article, we intend to analyze the characteristics of this flow, the spaces in the city where they live and circulate, as well as their impacts on everyday life in the destination city. To cover the trajectory of immigrants, fieldwork was carried out in a public school in the city, in the EJA (Youth and Adult Teaching) modality. From an ethnographic research, which involves interviews and life stories of migrants, we describe their daily life in the city, we analyze the speeches related to prejudice and discrimination with the referred migratory flow and the challenges for the reception in a city that builds its identity around German immigrants who arrived in the city in the 19th century.
Keywords: migration; baianos; black; prejudice; Brusque